Single primer amplification (SPA) of cDNA for microarray expression analysis - Smith, Lee (Oxford University Press, 2003)
The potential of expression analysis using cDNA microarrays to address complex problems in a wide variety of biological contexts is now being realised. A limiting factor in such analyses is often the amount of RNA required, usually tens of micrograms. To address this problem researchers have turned to methods of improving detection sensitivity, either through increasing fluorescent signal output per mRNA molecule or increasing the amount of target available for labelling by use of an amplification procedure. We present a novel DNA-based method in which an oligonucleotide is incorporated into the 3′ end of cDNA during second-strand cDNA synthesis. This sequence provides an annealing site for a single complementary heel primer that directs Taq DNA polymerase amplification of cDNA following multiple cycles of denaturation, annealing and extension. The utility of this technique for transcriptome-wide screening of relative expression levels was compared to two alternative methodologies for production of labelled cDNA target, namely incorporation of fluorescent nucleotides by reverse transcriptase or the Klenow fragment. Labelled targets from two distinct mouse tissues, adult liver and kidney, were compared by hybridisation to a set of cDNA microarrays containing 6500 mouse cDNA probes. Here we demonstrate, through a dilution series of cDNA derived from 10 µg of total RNA, that it is possible to produce datasets comparable to those produced with unamplified targets with the equivalent of 30 ng of total RNA. The utility of this technique for microarray analysis in cases where sample is limited is discussed.